Visualization in modern cartography - MacEachren, Alan M., 1952-; Taylor, D. R. F. (David Ruxton Fraser), 1937-; ScienceDirect eBooks (Oxford, U.K. ; New York : Pergamon, 1994)
Visualization in Modern Cartography explores links between the centuries-old discipline of cartography and today's revolutionary developments in scientific visualization. The book has three main goals: (1) to pass on design and symbolization expertise to the scientific visualization community - information that comes from centuries of pre-computer <Q>visualization</Q> by cartographers, and their more recent experiences with computerizing the discipline; (2) to help cartographers cope with the dramatic shift from print cartography to a dynamic virtual cartography for which their role is changing from that of map designer to one of spatial information display (and/or interface) designer; (3) to illustrate the expanded role for cartography in geographic, environmental, planning, and earth science applications that comes with the development of interactive geographic visualization tools. To achieve these goals, the book is divided into three parts. The first sets the historical, cognitive, and technological context for geographic/cartographic visualization tool development. The second covers key technological, symbolization, and user interface issues. The third provides a detailed look at selected prototype geographic/cartographic visualization tools and their applications.
Introducing Geographic Visualization (GVIS) -- 1. Visualization in Modern Cartography: Setting the Agenda / Alan M. MacEachren -- 2. Visualization in Historical Context / Michael Wood -- 3. Cognitive Issues in Cartographic Visualization / Michael P. Peterson -- 4. The Bridge Between Cartographic and Geographic Information Systems / Kirsi Artimo -- 5. Interactive Multimedia for Mapping / William Cartwright -- 6. Visualization Software Tools / Terry A. Slocum, Marc P. Armstrong, Ian Bishop, John Carron, Jennifer Dungan, Stephen L. Egbert, Loey Knapp, Donna Okazaki, Theresa Marie Rhyne, Demetrius-Kleanthis D. Rokos, Amy J. Ruggles and Christopher R. Weber -- 7. Color Use Guidelines for Mapping and Visualization / Cynthia A. Brewer -- 8. Sound and Geographic Visualization / John B. Krygier -- 9. Designing a Visualization User Interface / Mikko Lindholm and Tapani Sarjakoski -- 10. Expert/Novice Use of Visualization Tools / Carol McGuinness.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Elsevier
Keywords: Cartography; Visualization; Cartographie; Visualisation; Cartography; Visualization; Visualisatie; Cartografie; Cartografia; Cartographie; Visualisation; Computerkartografie; Kartografische Darstellung; Visualisierung; Cartographie -- Méthodes graphiques; Visualisation; Aufsatzsammlung; Cartography -- Use of -- Computers; Electronic books